Analysis of the Spread of Communicable and Non Communicable Disease: Malaria and COVID-19 in Haldia City, West Bengal–A Spatial Approach for Epidemiological Analysis - Pijush Kanti Tripathi (The Bioscan, 2024)
The spread of communicable diseases like malaria and COVID-19 has significant impacts on public health, economies, and communities. Geographers, with their expertise in spatial analysis and Geographic Information Systems (GIS), play a pivotal role in mapping disease patterns, identifying risk factors, and guiding public health interventions. This paper aims to analyze the role of geographers in understanding the spread of these diseases in Haldia City, West Bengal, through a spatial epidemiological approach using GIS and spatial analysis techniques. The GIS analysis revealed that malaria cases were concentrated in certain rural districts with dense vegetation and stagnant water bodies. The spatial regression analysis demonstrated a strong correlation between environmental factors, such as high rainfall and temperature, and malaria incidence. The temporal GIS analyses indicated that vector control measures led to a reduction in malaria incidence in targeted areas. The results from the temporal analysis showed that environmental factors such as population density, mobility patterns, and proximity to healthcare facilities were significant predictors of disease spread. These findings underscore the importance of targeted public health intervention, including enhancing workplace safety, promoting social distancing, and improving ventilation, particularly in high-risk areas, to effectively control the spread.